2016
DOI: 10.3389/fphys.2016.00525
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Characterization of Dynamic Parameters of Intracellular Calcium Signals

Abstract: Dynamic processes, such as intracellular calcium signaling, are hallmark of cellular biology. As real-time imaging modalities become widespread, a need for analytical tools to reliably characterize time-series data without prior knowledge of the nature of the recordings becomes more pressing. The goal of this study is to develop a signal-processing algorithm for MATLAB that autonomously computes the parameters characterizing prominent single transient responses (TR) and/or multi-peaks responses (MPR). The algo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 86 publications
0
20
0
Order By: Relevance
“…Insights from ‘semi quantitative assays’ of [Ca 2+ ] i levels at baseline together with parameters describing ligand-induced transients and/or oscillations are much needed. These can be obtained by using recently published analytical software [ 93 ]. In other cell and tissue systems, a strong emphasis on details of [Ca 2+ ] i transient waveforms has yielded interesting insights into some aspects of [Ca 2+ ] i homeostasis [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Insights from ‘semi quantitative assays’ of [Ca 2+ ] i levels at baseline together with parameters describing ligand-induced transients and/or oscillations are much needed. These can be obtained by using recently published analytical software [ 93 ]. In other cell and tissue systems, a strong emphasis on details of [Ca 2+ ] i transient waveforms has yielded interesting insights into some aspects of [Ca 2+ ] i homeostasis [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regions of interest (ROI) were manually defined and the ratio of the fluorescent emission at 510 nm, following 340 and 380 nm excitation (f340/f380), was calculated and exported using the imaging software (Volocity, Improvision). All data were imported into an excel spreadsheet for characterization using a MATLAB algorithm previously described ( Mackay et al, 2016 ). The following parameters were obtained for statistical analysis: amplitude (amp; magnitude of response), activation time (t 10%-90% ; time between 10% and 90% of maximum response), and decay constant (τ decay ) of exponential decay region of deactivation phase of transient response.…”
Section: Methodsmentioning
confidence: 99%
“…We found that Rab5-silenced cells tend to delay both, the serum-induced time to reach the maximal responses of Ca 2C signal (signal peak of Ca 2C , Fig. 2G) and the serum-induced activation time (lapsed time for Ca 2C signal to increase from 10% to 90% of the maximal response, 28 Fig. 2H) when compared to control cells.…”
Section: Rab5 Is Required For Calpain2 Activationmentioning
confidence: 83%